2021
DOI: 10.31234/osf.io/qwae4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cohort differences in aging self-perceptions among Japanese older adults

Abstract: This study examined cohort differences in levels and health effects of aging self-perceptions among older individuals. Using longitudinal data collected in Japan during 1987–2006, we compared two cohorts born in the 1920s versus the 1930s. To control for relevant covariates, we identified case-matched controls based on age and gender (age range = 60–65 years; n = 515 per cohort). Self-perceptions of aging were measured at baseline. Health outcome was indexed as functional impairment for 9–10 years. Regression … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…In South Korea, for example, research has found a tendency towards negative self-perceptions of aging among older people, 48,49 with both intergenerational and spousal relations and contexts (including health status) being associated with one's self-perceptions of aging, thus, stressing the interdependence between family members. 50 There also are variations in self-perceptions of aging across different age cohorts, with younger Japanese cohorts reporting better self-perceptions of aging compared with older cohorts, 47 as well as variations across geographic areas, with rural Chinese older adults reporting poorer self-perceptions of aging. 44 These findings point to specific population groups that might benefit from further interventions as well as to the importance of addressing all family members when attempting to improve self-perceptions of aging, given the strong interdependence within families.…”
Section: Ageism and Filial Piety In The Western Pacific Regionmentioning
confidence: 99%
“…In South Korea, for example, research has found a tendency towards negative self-perceptions of aging among older people, 48,49 with both intergenerational and spousal relations and contexts (including health status) being associated with one's self-perceptions of aging, thus, stressing the interdependence between family members. 50 There also are variations in self-perceptions of aging across different age cohorts, with younger Japanese cohorts reporting better self-perceptions of aging compared with older cohorts, 47 as well as variations across geographic areas, with rural Chinese older adults reporting poorer self-perceptions of aging. 44 These findings point to specific population groups that might benefit from further interventions as well as to the importance of addressing all family members when attempting to improve self-perceptions of aging, given the strong interdependence within families.…”
Section: Ageism and Filial Piety In The Western Pacific Regionmentioning
confidence: 99%